Classification of the multigene family of fatty acid binding proteins (FABPs) and transcription profile of the genes in striped catfish (Pangasianodon hypophthalmus) - Binh, Le Thi Nguyen; Hoang, Tran Son; Trang, Tran Thi Huyen; Hoa, Nguyen Thi; Oanh, Kim Thi Phuong (Vietnam Journal of Biotechnology, 2021)
Striped catfish (Pangasianodon hypophthalmus) is an economically important fish in Vietnam. The catfish fillets contain high fatty acid composition. The FABP family is involved in lipid transport and metabolism as well as in the regulation of gene expression and cell development. In this study, the catfish genome database was searched for fabp gene family; then, gene structure, classification and phylogenetic relationships were analyzed. In striped catfish genome, we found 10 fabp genes that are homologous to other fish species and other 5 novel fabp genes that have not been clearly annotated. These newly identified fabp genes cluster separately from the known members of the fabp family on the phylogenetic tree, and further studies are needed to understand their roles and functions. We examined transcriptional gene expression of fabp3, fabp7 and fabp10a genes in muscle, liver and brain tissues of the stripped catfish. The results showed that fabp10a gene was not strongly expressed in all 3 types of tissues; fabp3 gene was most strongly expressed in liver tissue and fabp7 was highly up-regulated in brain tissue. The results of this study provide a resource for further research on the function of fabp genes and their genetic diversity in striped catfish.